Non-kinetic losses caused by electrochemical carbon corrosion in PEM fuel cells - Park, S.; Shao, Y.; Viswanathan, V.V.; Liu, J.; Wang, Y.
This paper presented non-kinetic losses in PEM fuel cells under an accelerated stress test of catalyst support. A cathode with carbon-supported Pt catalyst was prepared and characterized during potential hold at 1.2 V vs. SHE in a PEM fuel cell. Irreversible losses caused by carbon corrosion were evaluated using a variety of electrochemical characterizations including cyclic voltammetry, linear sweep voltammetry, electrochemical impedance spectroscopy, and polarization technique. Ohmic losses at the cathode during potential hold were determined using its capacitive responses. Concentration losses in the PEM fuel cell were analyzed in terms of Tafel behavior and thin ilm/flooded-agglomerate dynamics.
Keywords: PROTON EXCHANGE MEMBRANE FUEL; CELLS; CARBON CORROSION; NON-KINETIC LOSSES